The struggle of man, religious and social, as a central motif in the writings of S.Y. Agnon - Herczl, Moshe Y (Department of Religious Studies, 2016)
In this paper, we will assume that Agnon's writing has, in addition to its aesthetic and artistic value, also a clearly didactic intention, and in the course of this paper we will attempt to verify this assumption. There are therefore two basic assumptions at the heart of this paper. 1. There is a unity in Agnon's writing. 2. Agnon had didactic intention. The object of this paper is to clarify the nature of the unity and the intention: what is a unifying theme in the work, and what does it come to teach? Our thesis is that Agnon deals with the theme of man's struggle and conflict. His attitude to any character is in direct proportion to its willingness to take upon itself a direct confrontation with the . problems which it faces. We will attempt to show that this subject moves throughout Agnon's varied and diversified writings.